Reactivity of [M2(μ‐Cl)2(cod)2] (M=Ir, Rh) and [Ru(Cl)2(cod)(CH3CN)2] with Na[H2B(bt)2]: Formation of Agostic versus Borate Complexes. Issue 48 (18th October 2016) - Bakthavachalam, K.; Yuvaraj, K.; Zafar, Mohammad; Ghosh, Sundargopal
Abstract: Treatment of [M2 (μ‐Cl)2 (cod)2 ] (M=Ir and Rh) with Na[H2 B(bt)2 ] (cod=1, 5‐cyclooctadiene and bt=2‐mercaptobenzothiazolyl) at low temperature led to the formation of dimetallaheterocycles [(Mcod)2 (bt)2 ], 1 and2 (1 : M=Ir and2 : M=Rh) and a borate complex [Rh(cod)κ 2 ‐S, S′‐H2 B(bt)2 ], 3 . Compounds1 and2 are structurally characterized metal analogues of 1, 5‐cyclooctadiene. Metal–metal bond distances of 3.6195(9) Å in1 and 3.6749(9) Å in2 are too long to consider as bonding. In an attempt to generate the Ru analogue of1 and2, that is [(Rucod)2 (bt)2 ], we have carried out the reaction of [Ru(Cl)2 (cod)(CH3 CN)2 ] with Na[H2 B(bt)2 ]. Interestingly, the reaction yielded agostic complexes [Ru(cod)Lκ 3 ‐H, S, S′‐H2 B(bt)2 ], 4 and5 (4 : L=Cl;5 : L=C7 H4 NS2 ). One of the key differences between4 and5 is the presence of different ancillary ligands at the metal center. The natural bond orbital (NBO) analysis of1 and2 shows that there is four lone pairs of electrons on each metal center with a significant amount of d character. Furthermore, the electronic structures and the bonding of these complexes have been established on the ground of quantum‐chemical calculations. All of the new compounds were characterized by IR, 1 H, 11 B, 13 C NMR spectroscopy, and X‐ray crystallographic analysis. Abstract : Metalla‐cod or agostic? Reactions of [Ru(Cl)2 (cod)(CH3 CN)2 ] and [Rh2 (μ‐Cl)2 (cod)2 ] with Na[H2 B(bt)2 ] form agostic complexes [Ru(cod)Lκ 3 ‐H, S, S′‐H2 B(bt)2 ] and the borate complex [Rh(cod)κ 2 ‐S, S′‐H2 B(bt)2 ] (L=Cl and C7 H4 NS2 ; bt=2‐mercaptobenzothiazolyl).